Job distribution in hierarchic systems - Lupin, Sergey; Sai Win Maw; Aye Min Thike; Kovalenko, Dmitry; Worden, John (2015 Internet Technologies and Applications (ITA), 2015)
This paper discusses options for using brute force methods for the distribution of complex tasks in hierarchical systems. The proposed algorithm is based on finding the optimal distribution of load between the executive elements at a predetermined structure. A simple hierarchic structure has been used as an example to investigate the functionality of the algorithm's software implementation.